Artifacts to avoid while taking advantage of top‐down mass spectrometry based detection of protein S‐thiolation. Issue 10 (17th April 2014) - Auclair, Jared R.; Salisbury, Joseph P.; Johnson, Joshua L.; Petsko, Gregory A.; Ringe, Dagmar; Bosco, Daryl A.; Agar, Nathalie Y. R.; Santagata, Sandro; Durham, Heather D.; Agar, Jeffrey N.
<x xml:space="preserve">Abstract</x> Bottom‐up MS studies typically employ a reduction and alkylation step that eliminates a class of PTM, S‐thiolation. Given that molecular oxygen can mediate S‐thiolation from reduced thiols, which are abundant in the reducing intracellular milieu, we investigated the possibility that some S‐thiolation modifications are artifacts of protein preparation. Cu/Zn‐superoxide dismutase (SOD1) was chosen for this case study as it has a reactive surface cysteine residue, which is readily cysteinylated in vitro. The ability of oxygen to generate S‐thiolation artifacts was tested by comparing purification of SOD1 from postmortem human cerebral cortex under aerobic and anaerobic conditions. S‐thiolation was ∼50% higher in aerobically processed preparations, consistent with oxygen‐dependent artifactual S‐thiolation. The ability of endogenous small molecule disulfides (e.g. cystine) to participate in artifactual S‐thiolation was tested by blocking reactive protein cysteine residues during anaerobic homogenization. A 50‐fold reduction in S‐thiolation occurred indicating that the majority of S‐thiolation observed aerobically was artifact. Tissue‐specific artifacts were explored by comparing brain‐ and blood‐derived protein, with remarkably more artifacts observed in brain‐derived SOD1. Given the potential for such artifacts, rules of thumb for sample preparation are provided. This study demonstrates that without taking extraordinary precaution, artifactual S‐thiolation of highly reactive, surface‐exposed, cysteine residues can result.